Peran Etika Profesi dalam Pengambilan Keputusan Manajerial :Analisis pada Fungsi Rekrutmen dan Seleksi SDM - Dito Aditia Darma; Hari Adrian Tarigan; Hendra Setiawan; Rafi Husni Alfajri Siregar; Zulkifli (MES Management Journal, 2026)
Professional ethics plays a crucial role in managerial decision-making, particularly in the recruitment and selection of human resources (HR). This study aims to analyze the influence of professional ethics principles on the decision-making process in selecting suitable candidates, maintaining organizational integrity, and creating a fair and transparent work environment. The research employed a descriptive qualitative approach, with data collected through in-depth interviews with HR managers, observation of recruitment processes, and analysis of company policy documents related to codes of ethics and selection procedures. The findings indicate that the implementation of professional ethics has a significant impact on the quality of managerial decisions, including the reduction of bias, increased objectivity, and compliance with labor laws and regulations. Furthermore, professional ethics contributes to strengthening internal and external trust in the organization, enhancing corporate reputation, and supporting the sustainability of professional HR management. This study recommends that organizations consistently disseminate and enforce professional ethics standards, provide training for recruitment managers, and implement evaluation and monitoring mechanisms at every stage of the selection process. Thus, integrating professional ethics into managerial decision-making serves as a strategic foundation for the effectiveness and sustainability of the HR function.